Additive single atom values for thermodynamics II: Enthalpies, entropies and Gibbs energies for formation of ionic solids - Glasser, Leslie (2022)
In part I of this series we established optimised sum values, for each of the chemical elements, of formula volumes, of absolute entropies, and of constant pressure heat capacities, together with their temperature coefficients. These atom values, when summed for a chemical formula, provided zero-level estimates of the corresponding property of that chemical material. Atom sums have the particular advantage of being essentially complete because of the finite number of chemical elements and are of use in prediction and checking of values for chemical materials. However, this is at the expense of an inability to distinguish among isomers and phases with the same chemical formula nor do they allow for effects of atom interactions.